Circulating FGF18 is decreased in pleural mesothelioma but not correlated with disease prognosis - Berta Mosleh; Karin Schelch; Thomas Mohr; Thomas Klikovits; Christina Wagner; Lukas Ratzinger; Yawen Dong; Katharina Sinn; Alexander Ries; Walter Berger; Bettina Grasl‐Kraupp; Konrad Hoetzenecker; et al. (Thoracic Cancer, 2023)
Abstract Background Pleural mesothelioma (PM) is a relatively rare malignancy with limited treatment options and dismal prognosis. We have previously found elevated FGF18 expression in PM tissue specimens compared with normal mesothelium. The objective of the current study was to further explore the role of FGF18 in PM and evaluate its suitability as a circulating biomarker. Methods FGF18 mRNA expression was analyzed by real‐time PCR in cell lines and in silico in datasets from the Cancer Genome Atlas (TCGA). Cell lines overexpressing FGF18 were generated by retroviral transduction and cell behavior was investigated by clonogenic growth and transwell assays. Plasma was collected from 40 PM patients, six patients with pleural fibrosis, and 40 healthy controls. Circulating FGF18 was measured by ELISA and correlated to clinicopathological parameters. Results FGF18 showed high mRNA expression in PM and PM‐derived cell lines. PM patients with high FGF18 mRNA expression showed a trend toward longer overall survival (OS) in the TCGA dataset. In PM cells with low endogenous FGF18 expression, forced overexpression of FGF18 resulted in reduced growth but increased migration. Surprisingly, despite the high FGF18 mRNA levels observed in PM, circulating FGF18 protein was significantly lower in PM patients and patients with pleural fibrosis than in healthy controls. No significant association of circulating FGF18 with OS or other disease parameters of PM patients was observed. Conclusions FGF18 is not a prognostic biomarker in PM. Its role in PM tumor biology and the clinical significance of decreased plasma FGF18 in PM patients warrant further investigation.